Durability and Taxes: Market Structure and Quasi-Capital Market Distortion - Swan, Peter L. (Econometrica, 1981)
[Understanding of the relationship between producer choice of product qualities and consumer preferences has been enhanced by the development of models specialized to a particular quality attribute–durability. Durability choice is invariant with respect to market structure under certain conditions but capital market imperfections and income taxes can upset this strong independence result. Income taxes are shown to mimic the effect of a capital market distortion on a monopolist selling a durable. Moreover, contrary to previous results the tax can increase as well as lower durability. A tax on "true income" is neutral in its effect and hence tax reform provides an alternative to regulatory control of product life.]